Conductive metal oxide coated silicon carbon material and preparation thereof, and application of conductive metal oxide coated silicon carbon material in lithium ion battery
The conductive metal oxide is in-situ coated on the surface of the silicon carbon material, the negative electrode material of the lithium ion battery, through the alkoxide hydrolysis method and the two-stage calcination process, which solves the problems of poor charge transfer performance and complicated preparation process of the silicon carbon material, and achieves efficient charging of the material. Improved transmission and cycle stability.
Patent Information
- Application Number
- CN202411392527.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing lithium-ion battery negative electrode material, silicon carbon material, has poor charge transfer performance during the cycle process, is complicated in the preparation process, and has problems such as material volume expansion and repeated generation of solid electrolyte membranes, resulting in capacity attenuation.
The conductive metal oxide is coated on the surface of the silicon carbon material in situ using the alkoxide hydrolysis method, and a conductive metal oxide coating layer with free electrons and oxygen vacancies is constructed through a two-stage calcination process to reduce the resistivity and interface polarization of the material. Phenomenon.
It significantly improves the charge transmission capacity and cycle stability of silicon carbon materials, alleviate the phenomenon of interface polarization, and increase the capacity and comparison capacity of the capacity of materials at high current density.
Smart Images

Figure CN119361627A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a metal oxide-coated silicon-carbon material and a preparation method and application thereof, wherein the application is mainly as a negative electrode material for lithium-ion batteries. Background Art
[0002] Lithium-ion batteries have been used in all aspects of life due to their excellent properties such as high energy density, light weight, long life and no memory. However, with the vigorous development of new energy vehicles, traditional lithium-ion batteries can no longer meet the public's growing demand for power batteries. Therefore, further improving the energy density, fast charging and discharging performance and cycle stability of commercial lithium-ion batteries is imminent. Silicon is considered to be the most promising negative electrode material for the next generation of lithium-ion batteries due to its abundant reserves and ultra-high specific capacity (4200mAh·g-1), but its shortcomings are also obvious. As a common semiconductor, silicon itself has poor conductivity, and the volume expansion of the material is severe (~400%) during the cycle, which leads to material crushing, repeated generation of solid electrolyte membranes, and ultimately irreversible capacity decay.
[0003] The most common method is to reduce the particle size of silicon to buffer the huge volume change of the material during the lithium extraction process, or to wrap the carbon shell in the outer layer of the silicon particles, while slowing down the volume change of the internal silicon particles, further improving the conductivity of the material. For example, Fan et al. (Z. Fan, S. Zheng, S. He, Y. Ye, J. Liang, A. Shi, Z. Wang, Z. Zheng, Preparation of micron Si @ C anodes for lithium ion battery by recycling thelamellar submicron silicon in the kerf slurry waste from photovoltaic industry, Diamond & Related Materials, 107 (2020) 107898.) prepared a silicon-carbon material with a core-shell structure of about 1 μm in diameter by a hydrothermal method, providing sufficient space for the expansion of the silicon material. At the same time, the carbon material enhances the conductivity of the composite material, and the capacity retention rate of the composite material after coating is significantly improved. At a current density of 0.1C, after 200 cycles, the capacity of the pure silicon wafer material has dropped to below 100mA h g-1, while the capacity of the composite material can reach 1788.9mA h g-1. In the rate performance test, the capacity of the composite material can reach 1446.8mA h g-1 at a current density of 1C, which is a significant improvement. However, the test conditions for the materials obtained by this technology are relatively mild, with a small current density (0.1C) and a short test cycle (100 cycles), which is not conducive to reflecting the application of the material in actual scenarios; and the hydrothermal temperature in this technical route reaches 190°C, and the corresponding pressure in the container reaches more than 1MPa. These factors are not conducive to the commercial application of this material.
[0004] Metal oxides are also considered to be applicable to lithium-ion batteries due to their high specific capacity, among which tin oxide (SnO 2) has attracted strong attention from scientific researchers. Antimony-doped tin oxide (ATO) is widely popular in the fields of advanced functional materials such as photovoltaics, catalysis, and energy storage devices due to its high optical transparency, good conductivity, high cycle stability, and low cost. For example, Zhang et al. (Q. Zhang, Q. Gao, W. Qian, H. Zhang, W. Tian, Z. Li, A C-coated and Sb-doped SnO2 nanocompsite with high surface area and low charge transfer resistance as ultrahigh capacity lithium ion battery anode, Materials Today Energy, Materials Today Energy, 13 (2019) 93-99.) prepared ATO powder by hydrothermal method, and then coated glucose by hydrothermal method and carbonized at high temperature to obtain ATO / C composite material (carbon-coated ATO). At a current density of 0.1C, its initial discharge capacity reaches 2634.9mA h g-1. After 1000 cycles at a current density of 1C, it can maintain a discharge capacity of 1008.5mA h g-1. The composite material can still maintain a reversible capacity of 370mA h g-1 at a high current density of 10C. The above effect may be related to the reduction of charge transfer resistance of the composite material by antimony doping and carbon coating. However, this technology uses ATO material as the main material to provide the capacity of the negative electrode material, which is expensive in itself. In addition, this technical route uses hydrothermal reaction to synthesize ATO powder. The reaction process is high temperature and high pressure, and the high pressure resistance requirements of the container are high.
[0005] Chinese invention patent application CN116632223A discloses a metal-doped amorphous carbon-coated silicon-carbon material and its preparation method and application; the material includes a core structure and a shell structure coated on the core structure; wherein the core structure includes porous carbon particles and nano-silicon grains deposited inside the porous carbon by silane cracking method; the shell structure includes metal and amorphous carbon generated by cracking of organic metal compounds. Preparation steps: Step S1), placing porous carbon in a vapor deposition furnace, passing silane mixed gas into the vapor deposition furnace for at least 1 hour, depositing nano-silicon inside the porous carbon, and obtaining porous carbon deposited with nano-silicon; Step S2), transferring the porous carbon deposited with nano-silicon obtained in the above step S1) to a vacuum reactor, passing an organic metal compound in a gasified state into the vacuum reactor for deposition; Step S3), obtaining the metal-doped amorphous carbon-coated silicon-carbon material. This technology utilizes the reducing property of carbon to deposit metal on the surface of silicon-carbon material, improves the electron transmission capacity of the composite material, and improves the cycle stability and first coulomb efficiency of the composite material to a certain extent. However, the deposition process of organic metal compounds in this technology needs to be carried out under vacuum conditions in order to prevent the oxidation of extremely small metals, increase the cracking reaction rate and prevent the introduction of impurities; and the silane cracking method is flammable and explosive, the process is dangerous, and has high requirements for production equipment. These factors have restricted the commercial application of this technical route. On the other hand, nanometal materials (such as Cu and Ni) are prone to react with electrolytes during long-term cycles, resulting in electrode failure or performance degradation. Especially at high potentials, some metals are prone to electrochemical corrosion or dissolution, which may cause degradation of the electrolyte and lead to electrode failure. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of poor charge transfer performance and complex preparation process of existing silicon-carbon materials, and to provide a conductive metal oxide-coated silicon-carbon material and a preparation method thereof which has simple process, low cost, good safety, environmental friendliness, good cycle stability and low capacity loss rate, and has the advantage of large-scale production.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] A method for preparing a metal oxide-coated silicon-carbon material, characterized by comprising the following steps:
[0009] 1) dispersing the silicon-carbon material, the reactive surface regulator, and the pH regulator in water by ultrasonication to obtain a reaction solution;
[0010] 2) dissolving the metal ion compound and the ligand in an alcohol solvent to form a coating solution; adding the coating solution to the reaction solution, heating to 70-95° C. and keeping the temperature for 2-6 hours to obtain a precursor slurry; the ligand is one or more of citric acid, tartaric acid and thioglycolic acid; the metal ion compound is tin tetrachloride pentahydrate, antimony trichloride or indium nitrate;
[0011] 3) After the precursor slurry is cooled, it is filtered under reduced pressure, dried, and washed;
[0012] 4) The washed precursor is calcined in two stages to obtain a metal oxide-coated silicon-carbon material; the first stage of the two-stage calcination is annealing and calcining at 180-250° C. in an air atmosphere, and the second stage of the calcination is annealing and calcining at 400-550° C. in an inert atmosphere for 1.5-3 hours.
[0013] To further achieve the purpose of the present invention, preferably, the reactive surface conditioner is one or more of oleyl alcohol, hexadecyltrimethylammonium bromide, sodium oleate and polyvinylpyrrolidone; the pH adjuster is one or more of urea, tetramethylammonium hydroxide and ammonium bicarbonate; the molar ratio of the pH adjuster to the metal ion compound is 3 to 8:1; the mass ratio of the silicon-carbon material to the reactive surface conditioner is 10 to 30:1.
[0014] Preferably, the alcohol solvent is one or more of ethanol, isopropanol, propylene glycol, methanol and butanol; the mass ratio of the metal ion compound to the ligand is 10 to 50:1; the mass ratio of the alcohol solvent to the metal ion compound is 10 to 60:1.
[0015] Preferably, the time of the first calcination is 50 to 90 minutes; the time of the second calcination is 1.5 to 3 hours; the heating rates of the first calcination and the second calcination are both 3 to 8°C / min.
[0016] Preferably, the ultrasonic dispersion time is 30 to 60 minutes, and the ultrasonic frequency is 20 to 90 KHz; the coating liquid is added to the reaction liquid under the action of a peristaltic pump; and the flow rate of the peristaltic pump is set to 0.5 to 3 ml / min.
[0017] Preferably, the silicon-carbon material is a core-shell structure in which a carbon shell encapsulates silicon particles, wherein the mass proportion of silicon particles is 40-90wt.%; the mass proportion of the carbon shell is 10-60wt.%;
[0018] The washing detergents are deionized water and ethanol; the drying temperature is 40 to 80° C., and the drying time is 12 to 24 hours.
[0019] A metal oxide-coated silicon-carbon material is prepared by the above preparation method.
[0020] The invention discloses an application of a metal oxide-coated silicon-carbon material as a negative electrode material for a lithium-ion battery.
[0021] Preferably, the application process is: the metal oxide-coated silicon-carbon material, carbon black and carboxymethyl cellulose or polyacrylic acid are mixed and then slurried, and then coated on copper foil to obtain a negative electrode sheet for a lithium-ion battery.
[0022] Preferably, the mass ratio of the metal oxide-coated silicon-carbon material, carbon black and carboxymethyl cellulose or polyacrylic acid is (6-8):(1-2):(1-2).
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] 1) The conductive metal oxide-coated silicon-carbon material of the present invention attaches the conductive metal oxide to the surface of the silicon-carbon material by hydrolysis of alcohol salts. The combination of the two significantly reduces the surface resistance of the silicon-carbon material, promotes electron transmission, weakens the polarization phenomenon of the material during the cycle, and improves the electrochemical properties of the silicon-carbon material.
[0025] 2) The present invention uses a two-stage calcination method. The first stage of air calcination makes most of the antimony element in the conductive metal oxide ATO exist in a pentavalent form, thereby providing more free electrons and holes and improving the conductive properties of the composite material.
[0026] 3) The present invention utilizes the strong conductivity of conductive metal oxides to form a coating with strong conductivity on the surface of silicon-carbon materials, thereby improving the electron transmission capacity of silicon-carbon materials and giving full play to the lithium storage capacity of composite materials. When the silicon-carbon material coated with conductive metal oxide synthesized by the present invention is applied to the negative electrode of lithium-ion batteries, when the silicon content is 85%, the electrochemical test results show that the material performs well compared with the control sample without manganese oxide particles: at 25°C, the current density is 2A·g-1 and the capacity can be maintained at 1053.53mAh·g-1 after 500 cycles; the capacity can be maintained at 842.23mAh·g-1 after 500 cycles at a current density of 4A·g-1, indicating that the material obtained by the present invention has excellent resistance to large current interference and lithium ion transmission capabilities, providing a good reference for the development of the field of fast charging and discharging of lithium-ion batteries.
[0027] 4) The conductive metal oxide-coated silicon-carbon material of the present invention presents a two-dimensional sheet stacking structure, the surface is evenly coated with nano-scale conductive metal oxides, and there are chemical bonds between the internal silicon sheets and the carbon shell to maintain the structural stability of the material.
[0028] 5) The conductive metal oxide-coated silicon-carbon material of the present invention is used as a high-performance lithium-ion battery negative electrode material, having the characteristics of excellent electron transfer rate, long cycle stability, slow capacity decay under high current density and high specific capacity, and has great application potential in the field of power batteries such as new energy vehicles.
[0029] 6) The technical route and method adopted by the present invention are simple, the process is simple, efficient, and low-cost, and the reagents used are safe and environmentally friendly, and have practical prospects for commercialization and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 This is the SEM image of the silicon powder used in Example 1.
[0032] Figure 2 This is the SEM image of the silicon-carbon material obtained in Example 1.
[0033] Figure 3 This is the SEM image of the ATO-coated silicon-carbon material prepared in Example 1.
[0034] Figure 4 This is the TEM image of the ATO-coated silicon-carbon material prepared in Example 1.
[0035] Figure 5 The XRD results of the ATO-coated silicon-carbon material and the silicon-carbon material prepared in Examples 1, 5, 7 and the comparative example are shown.
[0036] Figure 6 This is the full XPS spectrum of the ATO-coated silicon-carbon material prepared in Example 1.
[0037] Figure 7 This is the XPS high-resolution spectrum of Si 2p of the ATO-coated silicon-carbon material prepared in Example 1.
[0038] Figure 8 This is the XPS high-resolution spectrum of Sn 3d of the ATO-coated silicon-carbon material prepared in Example 1.
[0039] Fig. 9 This is the XPS high-resolution spectrum of C1s of the ATO-coated silicon-carbon material prepared in Example 1.
[0040] Fig.10 This is the CV diagram of the ATO-coated silicon-carbon material prepared in Example 1.
[0041] Fig.11 The ATO-coated silicon-carbon material prepared in Example 1 was heated to 2A g -1 Long cycle performance diagram at different current densities.
[0042] Fig.12 The ATO-coated silicon-carbon material prepared in Example 1 was heated to 4A g -1 Long cycle performance diagram at different current densities.
[0043] Fig.13 The ATO-coated silicon-carbon material prepared in Example 1 is 0.5-8.0A g -1 Rate performance diagram at different current densities.
[0044] Fig.14 This is a comparison chart of the EIS impedance after the first cycle of the ATO-coated silicon-carbon material obtained in Example 1 and the silicon-carbon material obtained in Comparative Example 1.
[0045] Fig.15 The resistivity data obtained by testing the resistivity of the ATO-coated silicon-carbon material obtained in Example 1 and the silicon-carbon material obtained in Comparative Example 1 by the four-probe method are compared.
[0046] Fig.16 This is the XRD result of the ATO-coated silicon-carbon material obtained in Comparative Example 3.
[0047] Fig.17 This is the TEM image of the ATO-coated silicon-carbon material obtained in Comparative Example 4. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. The present invention will be further described by way of examples, but the scope of protection of the present invention is not limited to these embodiments.
[0049] The terms used in this disclosure are only for the purpose of describing specific embodiments and are not intended to limit the disclosure. The singular forms of "a", "the" and "the" used in this disclosure are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0050] Unless otherwise specified, the raw materials used in the present invention are products that can be directly purchased on the market or synthesized by existing methods.
[0051] The submicron silicon-carbon material of the present invention is a core-shell structure of silicon particles wrapped in a carbon shell, wherein the mass proportion of silicon particles is 40-90wt.%; the mass proportion of the carbon shell is 10-60wt.%; the diameter of the silicon particles of the submicron silicon-carbon material is 100-800nm, and the thickness of the carbon shell is 8-12nm.
[0052] Synthesis of Si@C-1 material: See Chinese invention patent CN113644252B, in which Si@C material with core-shell structure is obtained by ball milling silicon powder with asphalt, spray drying and sintering with a coating machine.
[0053] Synthesis of Si@C-2 material: See Chinese invention patent CN110931725B, in which a core-shell structured Si@C material is obtained by hydrothermally mixing phenol, formaldehyde and amino-modified silicon nanoparticles and then calcining at high temperature after filtration.
[0054] Synthesis of Si@C-3 material: See Chinese invention patent application CN113328096A. Glucose, silicon powder and surfactant are placed in a reactor for hydrothermal reaction. After the reaction, the precursor is filtered and dried to obtain a precursor, and the precursor is calcined at high temperature to obtain a Si@C composite material with a core-shell structure.
[0055] The metal oxide-coated silicon-carbon material of the present invention is prepared by calcining a metal oxide precursor synthesized in situ on the surface of the silicon-carbon material in two stages; the metal oxide precursor synthesized in situ on the surface of the silicon-carbon material is prepared by dropping an organic mixed solution containing a metal inorganic salt into a mixed solution containing a silicon-carbon material that has been stirred at room temperature and ultrasonically treated, and then performing a hydrothermal reaction, followed by suction filtration and washing; specifically, the preparation method of the metal oxide-coated silicon-carbon material of the present invention comprises the following steps:
[0056] 1) dispersing the silicon-carbon material, the reactive surface regulator, and the pH regulator in water by ultrasonication to obtain a reaction solution;
[0057] 2) dissolving the metal ion compound and the ligand in an alcohol solvent to form a coating solution; adding the coating solution to the reaction solution, heating to 70-95° C. and keeping the temperature for 2-6 hours to obtain a precursor slurry; the ligand is one or more of citric acid, tartaric acid and thioglycolic acid; the metal ion compound is tin tetrachloride pentahydrate, antimony trichloride or indium nitrate;
[0058] 3) After the precursor slurry is cooled, it is filtered under reduced pressure, dried, and washed;
[0059] 4) The washed precursor is calcined in two stages to obtain a metal oxide-coated silicon-carbon material; the first stage of the two-stage calcination is annealing and calcining at 180-250° C. in an air atmosphere, and the second stage of the calcination is annealing and calcining at 400-550° C. in an inert atmosphere for 1.5-3 hours.
[0060] The main features of the metal oxide-coated silicon-carbon material and the preparation method thereof of the present invention are the two-stage calcination process of the selected metal ion compound and the in-situ growth of conductive metal oxide nanoparticles on the surface of the silicon-carbon material. The present invention realizes the in-situ growth of conductive metal oxide nanoparticles on the surface of the silicon-carbon material by the alcohol salt hydrolysis method; the method first dissolves the metal salt in an alcohol solvent to form a metal alcohol salt coating liquid, then introduces the coating liquid into the reaction liquid, and adds a ligand (also a complexing agent) to cooperate with the hydrolysis to complete the reaction process. During the hydrolysis process, the metal complex is an intermediate product of the reaction. The addition of the complexing agent (i.e., the ligand) can control the reaction rate, avoid the uneven precipitation caused by the addition of the alkaline precipitant due to the excessively high local alkalinity, so that it can be uniformly mixed at the atomic level, and finally the metal oxide is uniformly coated on the surface of the silicon-carbon material. Then, the present invention, through two-step annealing and calcination, on the basis of the carbon layer in the non-oxidized silicon-carbon material, incorporates a high-valent metal into another metal oxide lattice, and successfully constructs a conductive metal oxide-coated silicon-carbon material with free electrons and oxygen vacancies. The above two measures significantly reduce the resistivity and interface resistance of the metal oxide-coated silicon-carbon material of the present invention, improve the charge transfer capacity of the metal oxide-coated silicon-carbon material, promote the use of the capacity of the composite material at a higher current density, and alleviate the interface polarization phenomenon, thereby improving the cyclic stability of the material. In addition to the above two process measures, the selection of metal-containing inorganic salts, tetravalent tin salts, trivalent antimony salts (or trivalent indium salts) and ligands are important measures in the above two aspects. As for alcohol solvents, silicon-carbon materials, reactive surface regulators, pH regulators and their amounts, they can be selected in combination with the prior art under the purpose of the present invention, and other process conditions can also be selected in combination with the prior art under the purpose of the present invention through experiments. Among them, the preferred reactive surface regulator is one or more of oleyl alcohol, hexadecyltrimethylammonium bromide, sodium oleate and polyvinylpyrrolidone. The silicon-carbon material is a core-shell structure of silicon particles wrapped in a carbon shell, which is a material already available in the prior art, wherein the mass proportion of silicon particles is 40-90wt.%; the mass proportion of carbon shell is 10-60wt.%.
[0061] It should be noted that ATO material, as a conductive metal oxide, has been commercially applied in conductive glass and other fields, and researchers have made some attempts to coat silicon materials with ATO. Lee et al. (J. Lee, E. Lee, J. Park, S. Park, S. Lee, Ultrahigh-Energy-Density Lithium-ion Batteries Based on a High-Capacity Anode and a High-Voltage Cathode with an ElectroconductiveNanoparticle Shell, (2014) 8) stirred, filtered and calcined Si and the purchased finished ATO colloid to obtain Si@ATO composite material, which greatly improved its electron transmission capacity and effectively utilized the capacity of silicon material. However, due to the lack of carbon material coating, its cycle retention rate is poor; and the use of finished ATO coating will also cause uneven coating and high cost. In addition, the ATO material itself has the problem of low initial coulomb efficiency in the lithium storage process, which restricts its application.
[0062] The conductive metal oxide-coated silicon-carbon material of the present invention generates nano-scale conductive metal oxide powder in situ and coats the surface of the silicon-carbon material to form a conductive network, which more effectively improves the electron transmission capacity and greatly enhances the capacity of the composite material under high current density. By coating a small amount of ATO material on the surface and in the pores of the carbon material, the first coulombic efficiency of the target material does not decrease significantly. In particular, the precursor synthesis stage of the present invention is carried out at normal pressure and below 100° C., which has low requirements on instruments and equipment and low cost, and is very conducive to the low-cost large-scale production of silicon-carbon materials.
[0063] The present invention performs characterization methods such as X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and four-probe resistance measurement on the materials prepared in the examples and comparative examples to analyze information such as the morphology, component content, and type of chemical bonds of the materials.
[0064] Example 1
[0065] A method for preparing an ATO-coated silicon-carbon material comprises the following steps:
[0066] 1) Synthesis of silicon-carbon material: Referring to the method of Chinese invention patent CN113644252B, 1 kg of silicon powder and 200 g of asphalt were mechanically ball-milled for 4 h, added to a coating machine and calcined at 900 °C for 2 h to obtain a silicon-carbon material with a core-shell structure, and the obtained silicon-carbon material was named Si@C-1; Figure 1This is a SEM image of the silicon powder used in Example 1, and it can be observed that the submicron-level two-dimensional silicon wafer is obtained by sand grinding; Figure 2 This is the SEM image of the silicon-carbon material obtained in Example 1. After carbon coating, a silicon-carbon material with a size of submicron level is obtained. It can be observed that the carbon layer is uniformly coated on the surface of the silicon material. Figure 5 The XRD results of the silicon-carbon material Si@C-1 of this embodiment are shown.
[0067] 2) Take a beaker with a capacity of 100 ml, add 1.25 g of tin tetrachloride pentahydrate, 0.10 g of antimony trichloride, 0.04 g of tartaric acid, and 40 ml of ethanol, and stir to dissolve to obtain a coating solution;
[0068] 3) Take a beaker with a capacity of 1 liter, add 10g of silicon-carbon material, 0.5g of hexadecyltrimethylammonium bromide, 1.25g of urea, and 400ml of water into the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0069] 4) The reaction solution obtained in step (3) is heated to 90° C. in a water bath, and the coating solution obtained in step (2) is slowly dripped into the reaction solution using a peristaltic pump (the flow rate is set to 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 5 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0070] 5) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in a tube furnace under an air atmosphere and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated under an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-1 is obtained.
[0071] Figure 3 This is a SEM image of the ATO-coated silicon-carbon material obtained in Example 1. The SEM image shows that the final target material presents a two-dimensional submicron flaky structure.
[0072] Figure 4 This is the TEM image of the ATO-coated silicon-carbon material prepared in Example 1. In the image, Si-C-ATO layers arranged from the inside to the outside can be observed, which proves that the ATO-coated silicon-carbon material is obtained by hydrolysis of alcohol salts. The 3-5 nm ATO nanoparticles in the composite material are coated on the surface of the silicon-carbon material. The extremely small size of the nanoparticles also reduces the possibility of breakage of the ATO material during the cycle, constructs a unique and stable conductive network, and greatly contributes to the electronic transmission of the composite material. At the same time, the small gaps left between the nanoparticles form abundant lithium ion diffusion paths, which accelerate the electrolyte penetration process and allow the electrolyte to fully infiltrate the interior of the material.
[0073] Figure 5 The XRD results of the ATO-coated silicon-carbon material Si@C@ATO-1 prepared in Example 1 are also shown. SnO 2 The corresponding characteristic peaks and no Sb 2 O 5 The characteristic peaks of ATO and Sb appeared, proving the successful coating of ATO and the successful doping of Sb.
[0074] Figure 6 This is the XPS full spectrum of the ATO-coated silicon-carbon material Si@C@ATO-1 prepared in Example 1. The presence of ATO powder can be confirmed in the full spectrum.
[0075] Figure 7 This is the XPS high-resolution spectrum of Si 2p of the ATO-coated silicon-carbon material Si@C@ATO-1 prepared in Example 1. The existence of Si-OC bonds indicates that the Si and C layers are not in simple physical contact, but a more stable coating structure is formed by chemical bonds.
[0076] Figure 8 This is the XPS high-resolution spectrum of Sn 3d of the ATO-coated silicon-carbon material Si@C@ATO-1 prepared in Example 1. 5 / 2 and Sn 3d 3 / 2 The peaks indicate that Sn exists in the form of oxides.
[0077] Fig. 9 This is the XPS high-resolution spectrum of C1s of the ATO-coated silicon-carbon material Si@C@ATO-1 prepared in Example 1. The presence of CO bonds and C-Si bonds in the figure further confirms the stable structure of Si-C composed of chemical bonds.
[0078] Fig.10 This is the CV graph of the ATO-coated silicon-carbon material prepared in Example 1. The anodic peaks corresponding to 0.35V and 0.51V and the cathodic peak corresponding to 0.2V in the figure are characteristic peaks corresponding to the charge and discharge process of the silicon electrode, and as the cycle proceeds, the cathodic peak and the anodic peak are strengthened, proving the improvement of the electrochemical reaction kinetics of the electrode during the cycle.
[0079] The following examples are related to the raw materials, intermediate products and target products. Figure 1-10 Basically similar, not provided one by one.
[0080] Weigh 0.14 g of the prepared ATO-coated silicon-carbon material Si@C@ATO-1, 0.03 g of carboxymethyl cellulose binder, and 0.03 g of conductive carbon black, grind them thoroughly in a mortar and move them to a finger bottle, add 2 ml of distilled water, and after magnetic stirring for 12 hours, use a glass rod to coat the material on a flat copper foil. After the material is dried, press it into an electrode, use a metal lithium sheet as the counter electrode, and assemble it into a CR2016 button battery in a glove box.
[0081] Example 2
[0082] A method for preparing an ITO-coated silicon-carbon material comprises the following steps:
[0083] 1) Take a beaker with a capacity of 100 ml, add 1.055 g of indium nitrate pentahydrate, 0.1262 g of tin tetrachloride pentahydrate, 0.06 g of citric acid, and 40 ml of isopropanol, and stir to dissolve to obtain a coating solution;
[0084] 2) Take a beaker with a capacity of 1 liter, take 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.8 g of oleyl alcohol, 0.5 g of ammonium bicarbonate, and 400 ml of water, add them to the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0085] 3) The reaction solution obtained in step (2) is heated to 95° C. in a water bath, and the coating solution obtained in step (1) is slowly dripped into the reaction solution using a peristaltic pump (the flow rate is set to 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 2 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ITO precursor-coated silicon-carbon material;
[0086] 4) After the powdered ITO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated under an argon atmosphere for 30 minutes, and then heated to 550°C and kept warm for 2 hours. After cooling to room temperature, the ITO-coated silicon-carbon material Si@C@ITO is obtained.
[0087] The process of CR2016 button battery is the same as that in Example 1.
[0088] Example 3
[0089] A method for preparing an ATO-coated silicon-carbon material comprises the following steps:
[0090] 1) Synthesis of silicon-carbon materials: Referring to Z. Fan, S. Zheng, S. He, Preparation of micron Si@Canodes for lithium ion battery by recycling the lamellar submicron silicon in the kerf slurry waste from photovoltaic industry, Diamond and Related Materials, 107 (2020) 107898, 200 g of nano-Si sheets, 300 g of glucose, 5 g of CTAB and 3 L of water were placed in a reactor, reacted at 180 ° C for 5 h, filtered and dried, and calcined at 900 ° C for 2 h under Ar atmosphere to obtain a silicon-carbon material named Si@C-2.
[0091] 2) Take a beaker with a capacity of 100 ml, add 1.25 g of tin tetrachloride pentahydrate, 0.10 g of antimony trichloride, 0.05 g of thioglycolic acid, and 40 ml of methanol, and stir to dissolve to obtain a coating solution;
[0092] 3) Take a beaker with a capacity of 1 liter, add 10g of silicon-carbon material, 0.5g of sodium oleate, 1.0g of tetramethylammonium hydroxide, and 400ml of water into the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0093] 4) The reaction solution obtained in step (3) is heated to 90° C. in a water bath, and the coating solution obtained in step (2) is slowly dripped into the reaction solution using a peristaltic pump (flow rate set at 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 2.5 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0094] 5) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-2 is obtained.
[0095] The process of CR2016 button battery is the same as that in Example 1.
[0096] Example 4
[0097] A method for preparing an ATO-coated silicon-carbon material comprises the following steps:
[0098] 1) Synthesis of silicon-carbon materials: Referring to Chinese invention patent CN109817962A, 600 g of nano-Si sheets, 20 g of CTAB, 260 ml of ammonia water, 120 g of resorcinol, 190 ml of formaldehyde and 20 l of water were added into a reactor and heated to 80 ° C for 24 h. After the reaction, the mixture was filtered and dried and calcined at 900 ° C for 2 h under Ar atmosphere to obtain a core-shell structured Si@C composite material named Si@C-3.
[0099] 2) Take a beaker with a capacity of 100 ml, add 1.25 g of tin tetrachloride pentahydrate, 0.10 g of antimony trichloride, 0.04 g of tartaric acid, and 40 ml of butanol, and stir to dissolve to obtain a coating solution;
[0100] 3) Take a beaker with a capacity of 1 liter, add 10 g of silicon-carbon material, 0.5 g of polyvinyl pyrrolidone, 1.25 g of urea, and 400 ml of water into the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0101] 4) The reaction solution obtained in step (3) is heated to 85° C. in a water bath, and the coating solution obtained in step (2) is slowly dripped into the reaction solution using a peristaltic pump (the flow rate is set to 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 3 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0102] 5) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-3 is obtained.
[0103] The process of CR2016 button battery is the same as that in Example 1.
[0104] Example 5
[0105] A method for preparing an ATO-coated silicon-carbon material comprises the following steps:
[0106] 1) Take a beaker with a capacity of 100 ml, add 2.5 g of tin tetrachloride pentahydrate, 0.20 g of antimony trichloride, 0.12 g of tartaric acid, and 40 ml of propylene glycol, and stir to dissolve to obtain a coating solution;
[0107] 2) Take a beaker with a capacity of 1 liter, take 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.5 g of hexadecyltrimethylammonium bromide, 2.5 g of urea, and 400 ml of water, add them to the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0108] 3) The reaction solution obtained in step (2) is heated to 80° C. in a water bath, and the coating solution obtained in step (1) is slowly dripped into the reaction solution using a peristaltic pump (flow rate set at 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 3.5 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0109] 4) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-4 is obtained. Figure 5 The XRD results of the ATO-coated silicon-carbon material Si@C@ATO-4 prepared in Example 1 are also shown. The characteristic peaks in the figure are consistent with those of the standard card. 2 The corresponding characteristic peak intensity increases relative to Si@C@ATO-1, proving the increase in ATO coating amount.
[0110] The process of CR2016 button battery is the same as that in Example 1.
[0111] Example 6
[0112] A method for preparing an ATO-coated silicon-carbon material comprises the following steps:
[0113] 1) Take a beaker with a capacity of 100 ml, add 3.75 g of tin tetrachloride pentahydrate, 0.30 g of antimony trichloride, 0.12 g of tartaric acid, and 40 ml of ethanol, and stir to dissolve to obtain a coating solution;
[0114] 2) Take a beaker with a capacity of 1 liter, take 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.5 g of hexadecyltrimethylammonium bromide, 3.75 g of urea, and 400 ml of water, add them to the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0115] 3) The reaction solution obtained in step (2) is heated to 75° C. in a water bath, and the coating solution obtained in step (1) is slowly dripped into the reaction solution using a peristaltic pump (the flow rate is set to 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 4 hours. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 hours to obtain a powdered ATO precursor-coated silicon-carbon material.
[0116] 4) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-5 is obtained.
[0117] The process of CR2016 button battery is the same as that in Example 1.
[0118] Example 7
[0119] A method for preparing an ATO-coated silicon-carbon material comprises the following steps:
[0120] 1) Take a beaker with a capacity of 100 ml, add 0.625 g of tin tetrachloride pentahydrate, 0.05 g of antimony trichloride, 0.02 g of tartaric acid, and 40 ml of ethanol, and stir to dissolve to obtain a coating solution;
[0121] 2) Take a beaker with a capacity of 1 liter, take 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.5 g of hexadecyltrimethylammonium bromide, 0.625 g of urea, and 400 ml of water, add them to the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0122] 3) The reaction solution obtained in step (2) is heated to 70° C. in a water bath, and the coating solution obtained in step (1) is slowly dripped into the reaction solution using a peristaltic pump (flow rate set at 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 4.5 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0123] 4) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-6 is obtained. Figure 5 The XRD results of the ATO-coated silicon-carbon material Si@C@ATO-6 prepared in Example 1 are also shown. The characteristic peaks in the figure are consistent with those of the standard card. 2 The corresponding characteristic peak intensity decreases relative to Si@C@ATO-1, proving the decrease in ATO coating amount.
[0124] The process of CR2016 button battery is the same as that in Example 1.
[0125] Comparative Example 1 (Silicon-carbon material without metal oxide coating)
[0126] Synthesis of silicon-carbon material: Referring to the method in Chinese invention patent CN113644252A, 1 kg silicon powder and 200 g asphalt were mechanically ball-milled for 4 h, added to a coating machine and calcined at 900 °C for 2 h to obtain a silicon-carbon material with a core-shell structure, and the silicon-carbon material obtained by this step was named Si@C@1;
[0127] The process of CR2016 button battery is the same as that in Example 1.
[0128] Comparative Example 2 (Effect of Air Calcination)
[0129] 1) Take a beaker with a capacity of 100 ml, add 1.25 g of tin tetrachloride pentahydrate, 0.10 g of antimony trichloride, 0.04 g of tartaric acid, and 40 ml of ethanol, and stir to dissolve to obtain a coating solution;
[0130] 2) Take a beaker with a capacity of 1 l, add 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.5 g of hexadecyltrimethylammonium bromide, 1.25 g of urea, and 400 ml of water into the beaker, and mix them evenly by ultrasonication for 30 min to obtain a reaction solution;
[0131] 3) The reaction solution obtained in step (3) is heated to 90° C. in a water bath, and the coating solution obtained in step (2) is slowly dripped into the reaction solution using a peristaltic pump (the flow rate is set to 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 5 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0132] 4) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-7 is obtained.
[0133] The process of CR2016 button battery is the same as that in Example 1.
[0134] Comparative Example 3 (composition alloy coating)
[0135] 1) Take a beaker with a capacity of 100 ml, add 1.25 g of tin tetrachloride pentahydrate, 0.10 g of antimony trichloride, 0.04 g of tartaric acid, and 40 ml of ethanol, and stir to dissolve to obtain a coating solution;
[0136] 2) Take a beaker with a capacity of 1 l, add 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.5 g of hexadecyltrimethylammonium bromide, 1.25 g of urea, and 400 ml of water into the beaker, and mix them evenly by ultrasonication for 30 min to obtain a reaction solution;
[0137] 3) The reaction solution obtained in step (3) is heated to 90° C. in a water bath, and the coating solution obtained in step (2) is slowly dripped into the reaction solution using a peristaltic pump (the flow rate is set to 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 5 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0138] 4) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated under an argon atmosphere for 30 minutes, and then heated to 750°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-8 is obtained.
[0139] The process of CR2016 button battery is the same as that in Example 1.
[0140] Comparative Example 4 (changing the reaction steps and using coprecipitation method)
[0141] 1) Take a beaker with a capacity of 1 liter, add 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.5 g of hexadecyltrimethylammonium bromide, and 400 ml of water into the beaker, and mix them evenly by ultrasonication for 30 minutes to obtain a reaction solution;
[0142] 2) Add 1.25 g of tin tetrachloride pentahydrate, 0.10 g of antimony trichloride and 0.04 g of tartaric acid into the reaction solution;
[0143] 3) Use a peristaltic pump (flow rate set at 2 ml / min) to drop 10 ml of ammonia water (25%) into the obtained reaction solution (stirring continuously during the dropping process). After the dropping is completed, heat to 90°C and keep warm for 2 hours; after the reaction is completed, cool to room temperature and filter, wash three times with deionized water and anhydrous ethanol respectively, place in an oven at 60°C and dry for 24 hours to obtain a powdered ATO precursor-coated silicon-carbon material;
[0144] 4) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 500°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-9 is obtained.
[0145] The process of CR2016 button battery is the same as that in Example 1.
[0146] Comparative Example 5 (No Sb doping)
[0147] 1) Take a beaker with a capacity of 100 ml, add 1.25 g of tin tetrachloride pentahydrate and 40 ml of ethanol and stir to dissolve to obtain a coating solution;
[0148] 2) Take a beaker with a capacity of 1 l, add 10 g of the silicon-carbon material obtained in step (1) of Example 1, 0.5 g of hexadecyltrimethylammonium bromide, 1.25 g of urea, and 400 ml of water into the beaker, and mix them evenly by ultrasonication for 30 min to obtain a reaction solution;
[0149] 3) The reaction solution obtained in step (3) is heated to 90° C. in a water bath, and the coating solution obtained in step (2) is slowly dripped into the reaction solution using a peristaltic pump (the flow rate is set to 2 ml / min). After the dripping is completed, the solution is kept warm and refluxed for 5 h. After the reaction is completed, the solution is cooled to room temperature and filtered, and washed three times with deionized water and anhydrous ethanol respectively, and placed in an oven at 60° C. for 24 h to obtain a powdered ATO precursor-coated silicon-carbon material.
[0150] 4) After the powdered ATO precursor-coated silicon-carbon material is evenly spread in a porcelain boat, it is heated to 250 degrees Celsius in an air atmosphere in a tube furnace and kept warm for 1.5 hours. Subsequently, the tube furnace is ventilated in an argon atmosphere for 30 minutes, and then heated to 650°C and kept warm for 2 hours. After cooling to room temperature, the ATO-coated silicon-carbon material Si@C@ATO-10 is obtained.
[0151] The process of CR2016 button battery is the same as that in Example 1.
[0152] Performance test: The present invention tests the resistance of the material surface, long cycle stability, resistance to large current interference and lithium storage performance through constant current charge and discharge, rate performance test, impedance and long cycle test. After the batteries prepared in the present invention are left for 24 hours, they are all tested using a battery tester (Shenzhen Xinwei) and BTS 8.0.0 software, with the test temperature at 25°C and the current density at 0.2-8A g -1 , various types of batteries are charged and discharged at constant current (discharge cut-off voltage is 0.01V, charge cut-off voltage is 2V) to test the long-term cycle performance of the battery.
[0153] Table 1 shows the electrochemical performance test results of the conductive metal oxide-coated silicon-carbon materials prepared in Examples 1-7 at 25°C.
[0154] Table 1
[0155]
[0156] Fig.11 The ATO-coated silicon-carbon material prepared in Example 1 was heated to 2A g -1 Long cycle performance diagram at different current densities. Fig.12 The ATO-coated silicon-carbon material prepared in Example 1 was heated to 4A g -1 Long cycle performance diagram under current density.
[0157]
[0158] The material exhibited good electrochemical performance, especially at high current density (4A g -1 ) under the condition of high specific capacity, the long cycle curve of the composite material electrode is gentle, showing a higher specific capacity and the capacity retention rate has made great progress compared with the control example.
[0159] Fig.13 The ATO-coated silicon-carbon material prepared in Example 1 is 0.5-8.0A g -1 The rate performance test diagram under current density is 8.0A g -1 A high charge specific capacity of 1034.21 can still be achieved at high current density, showing excellent rate performance. The rate performance is closely related to the electron transport capacity of the electrode, which proves that the electron transport capacity of the composite material has made great progress through coating.
[0160] Fig.14 This is a comparison diagram of the EIS impedance after the first cycle of the ATO-coated silicon-carbon material obtained in Example 1 and the silicon-carbon material obtained in Comparative Example 1. In the figure, the semicircle diameters corresponding to the electron transfer impedance and SEI film impedance of Example 1 are smaller than those of Comparative Example 1, which proves that the electron transfer impedance and SEI film impedance of the composite material are greatly reduced through ATO coating, which helps to improve the rate performance and cycle life of the battery and enhance the electrochemical reaction activity of the material.
[0161] Fig.15 The resistivity data of the ATO-coated silicon-carbon material obtained in Example 1 and the silicon-carbon material obtained in Comparative Example 1 were compared by four-probe method. The average resistivity of the sample obtained in Example 1 was 2522 Ωcm -1 The resistivity of the sample obtained in comparative example 1 is 6655Ωcm -1 The measured data further show that after ATO coating, the resistivity and electron transfer impedance of the composite material are greatly reduced. Fig.14 The eis impedance test results confirm each other.
[0162] Comparative Example 1 is a silicon-carbon material without ATO coating. Due to the high resistivity of the silicon-carbon material and the side reactions and polarization problems during the cycle process, it performs poorly in long cycle and rate performance tests.
[0163] Comparative Example 2 is a sample without two-stage calcination, which makes it difficult for Sb to be doped into SnO in pentavalent form. 2 Ultimately, it is impossible to successfully construct the highly conductive ATO coating on the silicon-carbon material, and the resistivity of the composite material is difficult to significantly reduce. Although the first coulombic efficiency of the composite material is improved compared to before coating, the capacity retention rate is poor during long cycles.
[0164] In comparative example 3, the calcination temperature was increased, so that the tin antimony oxide in the designed ATO coating layer was reduced by the carbon layer to generate a tin antimony alloy, and a tin antimony-tin metal coating structure was constructed. Fig.16 In the XRD result of Comparative Example 3, the peaks of tin-antimony alloy and tin appear, while the peaks of SnO 2 The peak does not appear, which confirms the metal coating. In such a coating layer, the alloy material may melt during the calcination process due to its low melting point and cannot form a dispersed conductive network to reduce the resistivity of the composite material; the metal may also undergo electrochemical dissolution during a long cycle; at the same time, tin oxide is prone to volume expansion and breakage during the cycle, all of which lead to the inability to form an effective conductive coating layer, resulting in a lower cycle retention rate and first coulomb efficiency.
[0165] Comparative Example 4 uses a coprecipitation method as a coating method. This coating method easily causes ATO to form floccules, which have poor crystallinity, and the particles are too small and cannot form a conductive network uniformly coated. Fig.17 This is the TEM image of the composite material of Comparative Example 4. In the image, it can be seen that the formed ATO particles are extremely small, less than 1 nm, with poor crystallinity and uneven coating. Such characterization results are mutually confirmed with the electrochemical performance.
[0166] Comparative Example 5 does not add antimony doping, and constructs the oxide SnO 2 As the structure of the coating layer, the comparative example found that its first coulombic efficiency and capacity retention rate were both low, which may be due to the SnO 2 The conductivity is poor and it is easy to expand and break during the cycle.
[0167] Comparing Examples 1 to 7 with Comparative Examples 1 to 5, it can be seen that the first coulombic efficiency of the embodiments is improved compared with the comparative examples. This is because the ATO coating reduces the resistivity of the composite material, and the ATO film on the surface also reduces the side reactions of the electrode material during the first charge and discharge process. It can be seen from the electrochemical performance test results in Table 1 that the reduction in resistivity, the enhancement of electron transmission performance, and the weakening of polarization effect ultimately lead to the long cycle retention rate of the embodiment material at a current density of 2A g-1 being increased from about 70% to 76-81%, and from about 60-65% to 70-75% at a current density of 4A g-1; and in the rate performance test, at a high current density of 8A g-1, the charge specific capacity of the embodiment is increased by 150-300mAh g-1. Combined with the test characterization results shown in multiple figures, it is proved that the conductive metal oxide is successfully coated, the electron transmission capacity is improved, and the SEI impedance is reduced. Finally, the cycle stability and rate performance have been greatly improved.
[0168] The present invention adopts an alcohol salt hydrolysis method as a synthesis method and applies a two-step calcination to in-situ coat the conductive metal oxide ATO (ITO) on the surface of a silicon-carbon material to form a composite material. The coating of the conductive metal oxide significantly reduces the resistivity of the composite material, reduces the interface resistance of the silicon-carbon material, improves the charge transfer capacity of the composite material, promotes the use of the capacity of the composite material under a higher current density, alleviates the interface polarization phenomenon, and thus improves the cycle stability of the material.
[0169] The alcohol salt hydrolysis method adopted by the present invention does not involve high temperature, high pressure or vacuum reaction process and does not use vapor deposition method, so it is safe and efficient, and can uniformly coat the conductive metal oxide precursor on the surface of the silicon-carbon material, and is supplemented by two-step annealing and calcination. On the basis of the carbon layer in the non-oxidized silicon-carbon material, a high-valent metal is doped into another metal oxide lattice, and a conductive metal oxide-coated silicon-carbon material with free electrons and oxygen vacancies is successfully constructed; the raw materials and chemical reagents used are all common medicines and have environmentally friendly characteristics; in summary, the present invention has the potential for commercial large-scale production.
Claims
1. A method for preparing a metal oxide-coated silicon-carbon material, characterized in that The steps include: 1) dispersing the silicon-carbon material, the reactive surface regulator, and the pH regulator in water by ultrasonication to obtain a reaction solution; 2) dissolving the metal ion compound and the ligand in an alcohol solvent to form a coating solution; The coating liquid is added to the reaction liquid, and the mixture is heated to 70-95° C. and kept warm for 2-6 hours to obtain a precursor slurry; the ligand is one or more of citric acid, tartaric acid and thioglycolic acid; the metal ion compound is tin tetrachloride pentahydrate, antimony trichloride or indium nitrate; 3) After the precursor slurry is cooled, it is filtered under reduced pressure, dried, and washed; 4) The washed precursor is calcined in two stages to obtain a metal oxide-coated silicon-carbon material; the first stage of the two-stage calcination is annealing and calcining at 180-250° C. in an air atmosphere, and the second stage of the calcination is annealing and calcining at 400-550° C. in an inert atmosphere for 1.5-3 hours.
2. The method for preparing a metal oxide-coated silicon-carbon material according to claim 1, characterized in that: The reactive surface conditioner is one or more of oleyl alcohol, hexadecyltrimethylammonium bromide, sodium oleate and polyvinyl pyrrolidone; the pH adjuster is one or more of urea, tetramethylammonium hydroxide and ammonium bicarbonate; the molar ratio of the pH adjuster to the metal ion compound is 3 to 8:1; the mass ratio of the silicon-carbon material to the reactive surface conditioner is 10 to 30:
1.
3. The method for preparing a metal oxide-coated silicon-carbon material according to claim 1, characterized in that: The alcohol solvent is one or more of ethanol, isopropanol, propylene glycol, methanol and butanol; the mass ratio of the metal ion compound to the ligand is 10-50:1; the mass ratio of the alcohol solvent to the metal ion compound is 10-60:
1.
4. The method for preparing a metal oxide-coated silicon-carbon material according to claim 1, characterized in that: The time of the first calcination is 50 to 90 minutes; the time of the second calcination is 1.5 to 3 hours; the heating rates of the first calcination and the second calcination are both 3 to 8°C / min.
5. The method for preparing a metal oxide-coated silicon-carbon material according to claim 1, characterized in that: The ultrasonic dispersion time is 30-60 minutes, and the ultrasonic frequency is 20-90 KHz; the coating liquid is added to the reaction liquid under the action of a peristaltic pump; and the flow rate of the peristaltic pump is set to 0.5-3 ml / min.
6. The method for preparing a metal oxide-coated silicon-carbon material according to claim 1, characterized in that: The silicon-carbon material is a core-shell structure in which a carbon shell encapsulates silicon particles, wherein the mass of silicon particles accounts for 40-90wt.%; the mass of the carbon shell accounts for 10-60wt.%; The washing detergents are deionized water and ethanol; the drying temperature is 40 to 80° C., and the drying time is 12 to 24 hours.
7. A metal oxide-coated silicon-carbon material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
8. Use of the metal oxide-coated silicon-carbon material according to claim 7 as a negative electrode material for a lithium-ion battery.
9. Use of the metal oxide-coated silicon-carbon material as a negative electrode material for lithium-ion batteries according to claim 8, characterized in that The application process is: the metal oxide coated silicon carbon material, carbon black and carboxymethyl cellulose or polyacrylic acid are mixed and then slurried, and then coated on copper foil to obtain a negative electrode plate of a lithium ion battery.
10. The use of the metal oxide coated silicon carbon material as a negative electrode material for lithium ion batteries according to claim 9, characterized in that: The mass ratio of the metal oxide-coated silicon-carbon material, carbon black and carboxymethyl cellulose or polyacrylic acid is (6-8): (1-2): (1-2).
Citation Information
Patent Citations
Phenolic-resin-modified silicon-based negative electrode material for lithium ion battery and preparation method thereof
CN109817962A
A silicon-carbon composite material, its preparation method and application
CN110931725B
Preparation method of silicon-carbon composite material, silicon-based negative electrode material and lithium ion battery
CN113328096A
Silicon-carbon negative electrode material and preparation method thereof
CN113644252A
Silicon-carbon negative electrode material and preparation method thereof
CN113644252B
Cited By
Silicon-carbon negative electrode material coated with metal fluoride and preparation method of silicon-carbon negative electrode material
CN121641923A
A metal fluoride-coated silicon-carbon negative electrode material and a preparation method thereof
CN121641923B